Dependence on ultra-high doses of gabapentinoids: A case series - Arun Bansal; Bhavneesh Saini; Harman Rai; Jaskanwar S. Dhillon; Priyanka Bansal; Sumit Saini (Indian Journal of Psychiatry)
Gabapentinoids, including Gabapentin and Pregabalin, are increasingly misused, particularly by individuals with psychiatric comorbidities or prior substance use. This case series highlights three patients, including one adolescent, who developed dependence on ultra-high doses of Gabapentinoids. Presenting patterns included use for euphoria, self-medication, and anxiety relief. All cases fulfilled the ICD-11 criteria for substance dependence, with features including neuroadaptation, functional impairment, and physical complications like weight-gain and edema. Despite prior literature suggesting low addictive potential, our findings challenge this notion and underscore a need for tighter prescription monitoring, public awareness, and regulatory action, especially in North Indian states like Punjab.